(untitled) (Ágora Journal, 2026)
Racism persists in Brazilian society on several fronts, such as discrimination against African-rooted religions, which are often the victims of attacks and violence. Despite this, it is necessary to consider the importance of mobilizing normative protection, especially understanding religious freedom as a fundamental right guaranteed in art. 5, VI of the Constituição Federal, and which must be guaranteed to everyone equally, including African-rooted religions. The problem brought up is glimpsed from the “Mãe Quida” case, which contributes to demonstrating how violations of freedom of worship occur in a specific way for each local reality. Therefore, the aim of this paper is to analyze how the right to religious freedom is protected, taking into account the “Mãe Quida” case, which took place in Sergipe and led to accountability and compensation for the damage caused by public agents.